Tissue engineering small diameter blood vessels : fabrication of porous scaffold. - Lin, Annette Luhe. (2009)
The interest in tissue engineered small diameter blood vessels was sparked off by the need for cardiovascular grafts in surgeries. This project aims to fabricate a porous scaffold to allow the diffusion of nutrients and growth factors in a co-culture of smooth muscle and endothelial cells found in blood vessels. PCLLGA, a previously developed polymer, has good elasticity and mechanical properties but the solid material impedes the diffusion of macromolecules necessary for co-culture. Co-culture is important to determine the viability of the scaffold for clinical applications as a vascular graft. As the porous scaffold will be used for micro-patterning, salt leaching cannot be used to create pores as the pores produced are bigger than the micro-channels that will be used. Ideally,pores of around 5 to 10 μm are desired. However, to our knowledge, no one has successfully developed pores of a few microns in a photo-elastomeric polymer. In this project, a method was successfully developed to produce a porous tubular scaffold of about 20% porosity with solid PEG and PCLLGA.